The Impact of Counseling on Smoking Cessation in Cardiovascular Disease Patients - Muhammad Arif Khan; Ruqaia Gul; Erum Irshad (Kurdish Studies, 2024)
Smoking continues to be the primary preventable cause of morbidity and mortality in cardiovascular disease patients. Smoking is well established risk factor for coronary heart disease. Cessation of smoking decreases the incidence of cardiovascular disease as well as mortality and additional cardiac events. The present study aimed to examine the impact of counseling on smoking reduction or cessation in cardiovascular disease patients(CVD). We examined the effect of psychosocial intervention, including counseling, telephone assistance, and self-help materials, on male smokers with cardiovascular disease (CVD). Participants of the study were randomly selected 60 male smokers CVD patients from OPD of two cardiology hospitals and we used a pretest posttest design by randomly allocating the participants to the control and intervention groups. We used the cigarette dependence scale (CDS-12) which is a reliable and valid measure of nicotine dependence and measures the progress of the cessation intervention. The main study outcome was the reduction scores o on the questionnaire or cessation of smoking at follow ups.The results of the study reported that psychological intervention of counseling was effective in reducing smoking scores and cessation of smoking in CVD patients. The study highlighted the implementation of counseling program for smoking cessation in CVD management program can help reduce morbidity and control of this preventable risk factor. Due to the substantial consequences related to smoking, psychological intervention of counseling may assist CVD patients to stop smoking, especially those with a higher degree of nicotine dependence and those with difficulty in quitting smoking.